Hippocampus-Dependent Memory Formation: Do Memory Type-Specific Mechanisms Exist? - Keiko Mizuno; Karl Peter Giese (Elsevier, 2005)
Long-term memory (LTM) formation requires gene transcription and de novo protein synthesis. The transcription factor CREB is required for hippocampus-dependent LTM formation, and it is activated by several signaling pathways, including protein kinase A (PKA), the mitogen activated protein/extracellular signal-regulated kinases (MAPK or ERKs), and Ca2+/calmodulin kinases (CaMKs). However, it is unknown whether all types of hippocampus-dependent LTM use the same signaling to activate transcription, and whether the transcriptional output is the same. Here we present molecular genetic and behavioral studies to demonstrate that two types of hippocampus-dependent LTM formation, spatial and contextual, require different signaling molecules. This can be illustrated by the CaMK kinases, CaMKKα, and CaMKKβ, which have converse roles. CaMKKα is required for contextual and CaMKKβ is required for spatial LTM formation. This leads to the surprising conclusion that there are distinct types of hippocampus-dependent LTM, which differ in their underlying molecular mechanisms. Keywords:: hippocampus, cAMP-responsive element binding protein, signaling, Ca2+/calmodulin kinase, mouse genetics